Beta-blockers and chronic kidney disease: a literature review - I. E. Bachmakov; A. N. Fedoseev; V. E. Denisova (Качественная клиническая практика, 2024)
Chronic kidney disease (CKD) and cardiovascular diseases are widespread throughout the world and are closely related to each other. Sympathetic hyperactivity, characteristic of CKD, increases cardiovascular risk and accelerates the progression of kidney disease by activating beta-adrenergic receptors. Beta-blockers play an important role in preventing the negative effects of in creased activity of the sympathetic nervous system on the cardiovascular system and kidneys, can slow the progression of renal disease, and have proven effective in reducing overall and cardiovascular mortality and treatment of coronary heart disease, heart failure, arterial hypertension, and arrhythmias in patients with CKD. Despite this, beta-blockers are still underused in patients with CKD, especially in its later stages, including ESRD. Although there are currently no clear recommendations for the choice of any specific beta blocker in CKD, factors such as the CKD stage, presence of diabetes mellitus or reduced insulin sensitivity, and pharmacodynamics (cardioselectivity, α1-blocking- and vasodilating properties) and pharmacokinetic properties (metabolism, routes of elimination from the body, degree of binding to plasma proteins and dualizability) should be considered. At present, along with ACE inhibitors, AT1-receptor antagonists, and SGLT2 inhibitors, beta-blockers remain indispensable drugs for treating cardiovascular diseases with proven positive effects on the progression of kidney failure in patients with CKD. Their broader use in this population is expected to further reduce cardiovascular mortality and delay the initiation of renal replacement therapy.